La création dans l’espace public, laboratoire artistique de pratiques altermétropolitaines - Léna Aparis Jutard (Bulletin de l’Association de Géographes Français)
Through artistic creation outside dedicated venues, creation in public space modifies the modes of production of contemporary urban public spaces, and thus contributes to a renewal of the perception and uses of the city. These cultural and territorial counter-proposals produce social innovation since they transgress the established order by encouraging the sharing of urban spaces by artists and the public within a largely non-commercial framework. In this sense, street arts can be seen as a laboratory for altermetropolization through experimentation. However, the gradual institutionalization of this art world, and its ephemeral nature, deserve to be questioned, as this seems to limit its oppositional dimension.